Does broadband infrastructure boost employment? - Oliver Falck (IZA World of Labor, 2017)
Broadband infrastructure enables fast access to the internet, which, evidence suggests, has significant effects on economic growth. However, labor market related issues have not received as much consideration. These include quantifying employment effects of broadband infrastructure roll-out and questions about who exactly are the winners and losers in the labor market, and whether skills in information and communication technologies (ICT) are reflected in labor market outcomes such as wages. Understanding these complementary issues allows for policy conclusions that go beyond simply encouraging the subsidization of broadband internet infrastructure.
Keywords: E24; H54; O18; 330; internet; economic growth; employment; wages; skills